2018
DOI: 10.1039/c7sm02061a
|View full text |Cite
|
Sign up to set email alerts
|

Dissipative disassembly of colloidal microgel crystals driven by a coupled cyclic reaction network

Abstract: A plethora of natural systems rely on the consumption of chemical fuel or input of external energy to control the assembly and disassembly of functional structures on demand. While dissipative assembly has been demonstrated, the control of structural breakdown using a dissipative cycle remains almost unexplored. Here, we propose and realize a dissipative disassembly process using two coupled cyclic reactions, in which protons mediate the interaction between the cycles. We show how an ordered colloidal crystal,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 40 publications
0
23
0
Order By: Relevance
“…Recently, spiropyran (SP) and its derivatives have emerged as attractive building blocks for constructing artificial dynamic self‐assembled structures and materials [33–36] . In particular, merocyanine‐based photoacids have been used as light‐responsive regulators for generating dynamic assemblies from intrinsically non‐photoresponsive components [37–41] . Despite the numerous advantages of spiropyran and its derivatives as light‐responsive molecular switches, their use in the context of DNA nanotechnology has thus far not been demonstrated.…”
Section: Figurementioning
confidence: 99%
“…Recently, spiropyran (SP) and its derivatives have emerged as attractive building blocks for constructing artificial dynamic self‐assembled structures and materials [33–36] . In particular, merocyanine‐based photoacids have been used as light‐responsive regulators for generating dynamic assemblies from intrinsically non‐photoresponsive components [37–41] . Despite the numerous advantages of spiropyran and its derivatives as light‐responsive molecular switches, their use in the context of DNA nanotechnology has thus far not been demonstrated.…”
Section: Figurementioning
confidence: 99%
“…Water droplets could freely roll off the irradiated surface, suggesting possible applications in remotely controlled, self‐cleaning surfaces . Similarly, Kuehne and co‐workers demonstrated that the aggregation state of non‐photoresponsive microgel particles could be controlled by light in the presence of photoacid 3 (see Section ), whereas Santer and co‐workers showed that micrometer‐sized silica colloids could be assembled in the presence of an azobenzene surfactant (dubbed “photosoap”) in solution (compare with Section ).…”
Section: Extension To Microparticlesmentioning
confidence: 96%
“…The influence of this stimulus can be simply tuned without any contact by changing the wavelength, polarization direction and intensity . Taking advantage of this, a wide variety of chromophores including spiropyrans, o ‐nitrobenzyl derivatives, and azobenzene have been utilized to develop light‐sensitive polymers . Recently, increasing attempts have been made to synthesize microgel systems with chromophores included in their network to explore the potential of light stimulus for drug delivery applications …”
Section: Microgels For Drug Delivery Applicationmentioning
confidence: 99%
“…[137] Taking advantage of this, a wide variety of chromophores including spiropyrans, o-nitrobenzyl derivatives, and azobenzene have been utilized to develop light-sensitive polymers. [138][139][140] Recently, increasing attempts have been made to synthesize microgel systems with chromophores included in their network to explore the potential of light stimulus for drug delivery applications. [125] Light-responsive, 2,2,6,6-tetramethyl-1-piperidinyloxy (TEMPO)-oxidized Konjac Glucomannan (OKGM)-based delivery system was fabricated by Chen et al [135] The microspheres were stabilized by interaction between carboxylic (COO − ) groups and Fe 3+ ions.…”
Section: Remotely Controlled Microgels For Drug Deliverymentioning
confidence: 99%